Impact of age and symptom severity on parent-child relationships and self-perception among Chinese children with Attention Deficit Hyperactivity Disorder. Issue 5 (3rd September 2017) - Ma, Joyce L. C.; Lai, Kelly Y. C.; Lo, Julia W. K.
ABSTRACT: Little information is available on the effect of parent-child relationships on self-perception among Chinese children with Attention Deficit Hyperactivity Disorder (ADHD) in Hong Kong. This study examined the impact of children's age and symptom severity on the linkage of quality parent-child relationships to perceived competence/hope among children with ADHD. A clinical sample of 81 school-age children (ages 5–11, mean age = 8.38) who were diagnosed with ADHD were recruited in this study. Separate questionnaires were employed to collect data among children and their parents in the pre-treatment phase. Parent-child relationships were positively correlated with self-perception of children with ADHD, with physical competence to be father-child specific. Children's age had moderated the correlation between mother-child relationship and children's hope. Maternal role on children's hope was significant for the mild symptom group; paternal role on children's hope was significant for the severe symptom group. No moderation effect was found for symptom severity on the correlation between parent-child relationship and children's self-perception. The study's findings helped mental health professionals in a Chinese context to develop psychosocial interventions to foster quality parent-child relationships, which in turn will maintain children's self-perception. Implications for social work practice are discussed.